Psychometric Properties of the German Version of the Perception of Interprofessional Collaboration Model-Questionnaire (PINCOM-Q) - Astrid Jörns-Presentati and Gunter Groen and Atle Ødegård (International journal of integrated care, 2021)
Objective: The Perception of Interprofessional Collaboration-Model Questionnaire (PINCOM-Q) measures professionals’ perceptions of interprofessional collaboration in the field of child and youth mental health. The aim of this study was to validate the PINCOM-Q in a sample of German child welfare and child and youth mental health professionals.